Born to be young? Prenatal thyroid hormones increase early-life telomere length in wild collared flycatchers - Stier A; Hsu BY; Marciau C; Doligez B; Gustafsson L; Bize P; Ruuskanen S (The Royal Society Publishing, 2022)
4 years of post-growth telomere shortening). These findings suggest that prenatal THs might have a role in setting the 'biological' age at birth, but raise questions about the nature of the evolutionary costs of prenatal exposure to high TH levels.